2010
DOI: 10.2478/v10187-010-0059-7
|View full text |Cite
|
Sign up to set email alerts
|

Structural Evolution of Sputtered Indium Oxide Thin Films

Abstract: The indium oxide thin films were deposited at room temperature by reactive magnetron sputtering in the mixture of oxygen and argon on silicon and oxidized silicon substrates. The influence of the oxygen flow in the reactive mixture and post-deposition annealing on the structural properties were investigated. The as deposited In 2 O 3 films showed a dominating randomly oriented nanocrystalline structure of cubic In 2 O 3 . The grain size decreased with increasing oxygen concentration in the plasma. Annealing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 8 publications
1
6
1
Order By: Relevance
“…Both structures have been investigated using various deposition techniques such as atomic layer deposition (ALD), sputtering, chemical vapor deposition, laser ablation synthesis, and the sol–gel method . These previous studies reported that InO x generally formed a clear polycrystalline cubic structure with a preferred orientation of (211), (222), or (400), depending on the deposition method and process conditions. Among them, ALD has emerged as a promising deposition technique due to its low-temperature process, good uniformity, excellent step coverage, and controllability of material properties, such as the binding state and crystallinity . In addition, some previous studies have reported that the preferable electrical performance of ALD-processed InO x devices is comparable with those synthesized by a solution and sputtering because of the higher film density induced by a self-limited reaction on the growth surface. ,, For these reasons, the ALD-processed InO x film may be a promising active channel layer for the backplane of next-generation displays. ,, Yeom et al demonstrate the device with the high mobility of 39 cm 2 /V s using the Et 2 InN­(SiMe 3 ) 2 precursor, and Lee et al also present the InO x TFT device using the ([3-(dimethylamino)­propyl]­dimethyl indium) (DADI) precursor.…”
Section: Introductionmentioning
confidence: 99%
“…Both structures have been investigated using various deposition techniques such as atomic layer deposition (ALD), sputtering, chemical vapor deposition, laser ablation synthesis, and the sol–gel method . These previous studies reported that InO x generally formed a clear polycrystalline cubic structure with a preferred orientation of (211), (222), or (400), depending on the deposition method and process conditions. Among them, ALD has emerged as a promising deposition technique due to its low-temperature process, good uniformity, excellent step coverage, and controllability of material properties, such as the binding state and crystallinity . In addition, some previous studies have reported that the preferable electrical performance of ALD-processed InO x devices is comparable with those synthesized by a solution and sputtering because of the higher film density induced by a self-limited reaction on the growth surface. ,, For these reasons, the ALD-processed InO x film may be a promising active channel layer for the backplane of next-generation displays. ,, Yeom et al demonstrate the device with the high mobility of 39 cm 2 /V s using the Et 2 InN­(SiMe 3 ) 2 precursor, and Lee et al also present the InO x TFT device using the ([3-(dimethylamino)­propyl]­dimethyl indium) (DADI) precursor.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of oxygen reduced the crystallite size, consistent with previously reported results. 24,25 In the XPS analysis of the two films (Figure 3), which will be discussed in detail later, the amount of oxygen defects in the bulk of A1 is greater than that of A0. Due to the fact that oxygen defects in bulk lower the crystallinity, 26 the crystallite size of A1 is less than that of A0.…”
Section: ■ Introductionmentioning
confidence: 97%
“…In2O3 films prepared using different deposition methods may be single crystallinelike or polycrystalline but they mostly possess the cubic bixbyite structure independent of the substrate used [13]. The cubic bixbyite In2O3 structure is thermodynamically stable while the rhombohedral phase is the metastable phase [14,15]. The formation of rh-In2O3 requires high temperature and pressure conditions [12].…”
Section: Introductionmentioning
confidence: 99%